2021
DOI: 10.1007/s11869-021-01045-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of quantile regression into boosted regression trees (BRT) technique in forecasting emission model of PM10 concentration

Abstract: Air pollution is currently becoming a significant global environmental issue. The sources of air pollution in Malaysia are mobile or stationary. Motor vehicles are one of the mobile sources. Stationary sources originated from emissions caused by urban development, quarrying and power plants and petrochemical. The most noticeable contaminant in the Peninsular of Malaysia is the particulate matter (PM10), the highest contributor of Air Pollution Index (API) compared to other pollution parameters. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Contributions of independent variables and the marginal effect within the value range are clearly shown in the model results [59,60]. So far, BRT model has been successfully applied in urban heat island factor research [61,62], ecological risk assessment research [57,63] and many other fields, with high value.…”
Section: Boosted Regression Tree Modelmentioning
confidence: 89%
“…Contributions of independent variables and the marginal effect within the value range are clearly shown in the model results [59,60]. So far, BRT model has been successfully applied in urban heat island factor research [61,62], ecological risk assessment research [57,63] and many other fields, with high value.…”
Section: Boosted Regression Tree Modelmentioning
confidence: 89%
“…The highest value of R 2 was ranked as 1, the second highest value was ranked as 2, and the lowest was ranked as 3. Then, the ranked values for RMSE, NAE, and R 2 were summed up to find the lowest total ranking values among the three models, which indicate the best (Shaziayani et al, 2021).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Furthermore, there are many studies on the prediction of air pollutants concentration. However, most studies only focus on predicting one pollutant or a few pollutants only such as (Hamid et al, 2017;Shaadan et al, 2019;Alias et al, 2021;Shaziayani et al, 2021), and there is limited study on predicting all pollutants concentration in a study. Thus, this study will predict the concentration of all major air pollutants: ozone, carbon monoxide, nitrogen dioxide, sulfur dioxide, and particulate matter less than 10 micrometers (PM 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is progressively developing as a thorough method to the statistical analysis of linear and nonlinear models [11]. The QR represented the non-central location of a distribution which allow the approach to be more useful and precise [12]. [13] concluded that QR models inhibit some advantages compared to MLR since it does not rely on any properties, is independent or only mildly dependent, is robust to outliers, and is distribution free.…”
Section: Introductionmentioning
confidence: 99%